Competition, regulation and institutional quality - Raul V. Fabella (University of the Philippines, School of Economics (UPSE), 2017)
Regulation and competition policy are two alternative modalities by which the state intervenes in the market. In order for either to deliver welfare gains, there must first be a pre-existing market failure. We first present different varieties of market failures and identify those for which regulation is best address (cooperation failures such as The Fishing Game and the Public Goods Game, scale economies-based failures such as a Natural Monopoly and Meta-Market Failures) and those where competition policy works better (market power-based failures such as an artificial monopoly or cartel). We also discuss those market failures which cannot be remedied by an imperfect state. We show graphically the welfare outcomes of various industrial organizations (monopoly, duopoly, Walrasian limit) under the symmetric Cournot competition. We also deal with the welfare implications of imperfect substitutability. We then discuss some welfare implications of the Bertrand competition, its effect on innovation and on the formation of 'trusts'. We present reasons why competition policy is better than regulation in jurisdictions where institutions are weak. The reasons are: information intensity and asymmetry being greater with regulation, the greater ease of capture of the organs of regulation and, finally, the presence of private players who serve as allies of the competition agency and help monitor abuse of market power.
Keywords: K21; L51; L41; L44; 330; competition policy; regulation; weak institutions; market failures; Cournot competition; Bertrand competition